Study on the Ameliorative effects of Hydroxypropyl Betadex and Betadex Sulfobutyl ether sodium on acute ulcerative colitis induced by DSS in Mice - Lan Zhang; Fang Li; Huanhuan Wang; Bin Chen; Yongzhi Hua; Zhentao An (Carbohydrate Polymer Technologies and Applications)
Hydroxypropyl Betadex (HPB) and Betadex Sulfobutyl Ether Sodium (SEB) were widely employed as pharmaceutical excipients in oral and injectable formulations. This study investigated their therapeutic potential and underlying mechanisms in ulcerative colitis (UC) treatment. RAW264.7 cell experiments and DSS-induced acute UC mice assays were conducted to determine the effects of HPB and SEB on UC. Mechanistic investigations were conducted through network pharmacology, molecular docking, Caco-2 monolayer transepithelial electrical resistance (TEER) assays, and 16S rRNA sequencing of gut microbiota. Treatment with HPB or SEB reduced pro-inflammatory cytokines (NO, IL-6, and TNF-α) levels to 77.8 %-96.3 % of LPS-induced values in RAW264.7 cells. Compared with the DSS-induced UC model group, both HPB and SEB treatment groups showed significantly reduced levels of pro-inflammatory cytokines (TNF-α, IL-6, and IL-1β) (P < 0.01, P < 0.001). Network pharmacology predicted them to act on proteins related to inflammation. Molecular docking analysis revealed that HPB and SEB could function as “buffer”, demonstrating a tendency to form stable inclusion complexes with intestinal epithelial disruptors. Co-treatment with either (N-AT + HPB), (AMP + HPB), (N-AT + SEB), or (AMP + SEB) attenuated the TEER decline compared to the N-AT or AMP-only groups (P < 0.05). 16S rRNA sequencing showed that SEB and HPB regulated the disturbed diversity of intestinal flora. SEB and HPB were promising candidates for UC treatment, as they inhibited inflammatory pathways, formed epithelial disruptors inclusion, and regulated intestinal flora, providing valuable insights for the development of UC therapies.